2015
DOI: 10.20886/jped.2017.3.2.95-102
|View full text |Cite
|
Sign up to set email alerts
|

Keragaman Jenis Vegetasi Pada Hutan Bekas Kebakaran Di Taman Nasional Kutai, Kalimantan Timur

Abstract: ABSTRAKVegetasi hutan tropika basah di Kalimantan pada umumnya didominasi oleh jenis dari famili Dipterocarpaceae. Namun dengan adanya kebakaran hutan di beberapa wilayah di Kalimantan, telah mengakibatkan berubahnya komposisi vegetasi penyusun hutan. Penelitian ini bertujuan untuk mengetahui keanekaragaman jenis vegetasi pada hutan bekas kebakaran tahun 1982/1983 dan 1997/1998 di daerah Sangkima, Taman Nasional Kutai. Pengumpulan data keragaman jenis vegetasi dilakukan dengan membuat empat plot temporer beruk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…The index value of species diversity (H') indicates that this forest area has moderate species diversity, and there are certain species that dominate significantly, as indicated by the low value of the evenness index (E) (Table 1). When compared with the results of other studies on logged-over or burnt forest areas, the number of plant species in the study area was higher than that found in Sangkima [11] but lower when compared to the vegetation in Sungai Wain [12]. Based on the field observations, the PT Bara Tabang forest area has varied ecosystem conditions, including small hills, valleys, riparian, and riverbanks to the top of sandy hills.…”
Section: Species Compositionmentioning
confidence: 57%
“…The index value of species diversity (H') indicates that this forest area has moderate species diversity, and there are certain species that dominate significantly, as indicated by the low value of the evenness index (E) (Table 1). When compared with the results of other studies on logged-over or burnt forest areas, the number of plant species in the study area was higher than that found in Sangkima [11] but lower when compared to the vegetation in Sungai Wain [12]. Based on the field observations, the PT Bara Tabang forest area has varied ecosystem conditions, including small hills, valleys, riparian, and riverbanks to the top of sandy hills.…”
Section: Species Compositionmentioning
confidence: 57%
“…Kekayan jenis yang disediakan oleh BPDAS Kapuas jauh lebih kecil daripada kekayaan jenis di hutan arboretum PT Asmin Bronang, di Kabupaten Kapuas, yaitu 93 jenis, meskipun luasnya hanya 24 ha (Maimunah et al, 2020). Jumlah jenis yang 34 itu jauh lebih kecil daripada keyaan jenis pohon pada hutan bekas kebakaran di plot Taman Nasional Kutai, yaitu 163 jenis, meski luas plot yang disampel hanya 4 ha (Wahyudi et al, 2017) . Namun, kekayaan jenis yang disediakan BPDAS Kapuas jauh lebih tinggi daripada kekayaan jenis yang digunakan untuk rehabilitasi lahan kritis bekas penambangan yang biasanya tidak lebih dari tiga jenis (Munawar and Wiryono, 2015;Wiryono and Siahaan, 2013)), dan juga jauh lebih tinggi daripada hutan tanaman indidustri yang biasanya hanya dua jenis (BPS, 2020).…”
Section: Keragaman Jenisunclassified
“…This study aimed to analyze the species diversity and composition of seedlings for land rehabilitation in Kapuas Watershed, the reasons for species selection, and the location of seedling plantation and to compare the species compostion of seedlings for rehabilitation of degraded lnad in Kapuas Watershed dan Serayu-Opak-Progo Watershed. Three-year (2015-2016-2017) data of seedlings were gathered through questionnaire to Kapuas Watershed Management Agency. The data were analyzed quantitatively using a statistical software called Past.…”
mentioning
confidence: 99%